Knights & castles : a LEGO adventure in the real world - Arlon, Penelope; Gordon-Harris, Tory. (New York : Scholastic, 2016)
LEGO models and minifigures are illustrated in fun and fantastic scenarios describing knights and castles.
Includes index.
Keywords: Knights and knighthood -- Juvenile literature; Castles -- Juvenile literature; LEGO toys -- Juvenile literature; Knights and knighthood; Castles; LEGO toys; Castles; Knights and knighthood; LEGO toys; Castles; Knights and knighthood; LEGO toys; Juvenile works